The relationship of preterm and small for gestational age with child cognition during school-age years - Nguyen, Phuong Thi; Nguyen, Phuong Hong; Tran, Lan Mai; Khuong, Long Quynh; Nguyen, Son Van; Young, Melissa F.; DiGirolamo, Ann; Ramakrishnan, Usha (Elsevier, 2024)
Background Children born preterm and/or small for gestational age (SGA) are at increased risk of poor cognitive outcomes, particularly in low and middle-income countries (LMICs).